The role of policy labels, keywords and framing in transitioning waste policy. (1st March 2016) - Silva, Angie; Stocker, Laura; Mercieca, Paul; Rosano, Michele
Abstract: The last decade has seen a new wave of ambitious policies in order to address the mounting ecological damage caused by high levels of consumerism and the depletion of resources to manufacture short life-cycle products. In this paper 'Zero Waste' and 'Sustainable Materials Management' are examined as prominent labels of an evolving waste policy discourse towards waste prevention and reduction and material cycles. Using discourse analysis key documents are comparatively assessed, presenting the origins of these two concepts and how they entered the waste policy domain. The different framing tactics and governance models are then presented. The findings demonstrate that the different discourse paradigms around the concept of 'waste' and 'materials', influences what policy initiatives, measurement tools and outcomes are pursued. Although Zero Waste and Sustainable Materials Management are gaining popularity as indicators of shifting waste policy towards Sustainable Production and Consumption Policy, particularly with increasing discussion and application of Circular Economy governance models in Europe and China, a distinction still exists between the conceptualisation and implementation within and across the two concepts. It is in this transition towards a Circular Economy that it is valuable to review the role of policy labels, keywords and framing context in waste policy and the ability of enhanced waste management to assist in the development of more sustainable and environmentally acceptable economic and social behaviour models. Highlights: The transitioning of waste policy discourse and the emerging outcomes are presented. Zero Waste and Sustainable Materials Management are comparatively analysed. The current governance models erected to manage waste transitions are discussed. The findings suggest promoting policies with a materials rather than waste narrative.